Dynamic polarization of tumor-associated macrophages and their interaction with intratumoral T cells in an inflamed tumor microenvironment: from mechanistic insights to therapeutic opportunities - Han, Jiashu; Dong, Luochu; Wu, Mengwei; Ma, Fei (Frontiers in Immunology, 2023)
Immunotherapy has revolutionized tumor treatment in the last decades. However, many patients were unresponsive largely due to the immunosuppressive tumor microenvironment (TME). Tumor-associated macrophages (TAMs) have important roles in the formation and evolution of TME, marked by dual identities as both mediators and responders of inflammation. TAMs closely interact with intratumoral T cells, modulating infiltration, activation, expansion, effector function, and exhaustion. However, the heterogeneous and plastic nature of TAMs poses significant challenges for mechanistic studies and clinical translation of corresponding therapies. In this review, we summarize the mechanisms by which TAMs are dynamically polarized to modulate intratumoral T cells, including 1) interaction with other TME cells to shape a desmoplastic immune desert versus immunosuppressive myeloid-rich niche; and 2) direct reprogramming of T cells through surfaceome interaction, secretome signaling, and metabolic competition. Regarding each mechanism, we also discuss relevant therapeutic opportunities, encompassing non-specific and targeted approaches in conjugation with checkpoint inhibitors and cellular therapies, in the hope of developing macrophage-centered therapies to fine-tune tumor inflammation and empower immunotherapy.